서비스 기업의 종업원 만족도가 경영성과에 미치는 영향에 관한 연구 - 박정섭; Park, Jung-sub (Journal of distribution science, 2005)
For the customer satisfaction, the inside customer satisfaction must be made by offering the service of a good quality to the inside customer. If the inside customer is not satisfied with own business, the achievement of customer's loyalty & customer satisfaction which have direct effects on the performance of a corporation, comes to be difficult. This study tries to analyze what effect the inside customer satisfaction has on the yield performance of a corporation on the subject of the salespersons of the direct-control store among the retail store business.